THE HISTORY AND SPECIFIC LINGUISTIC FEATURES OF MAGIC SPELLS IN ENGLISH - Norbekova Gulrukh; Mirsanov Gaybulla (Journals Park Publishing, 2023)
This article explores the history and specific linguistic features of magic spells in the English language. It delves into the origins of spell casting, tracing its roots to ancient civilizations. The article also discusses the various types of spells, including love spells, protection spells, and healing spells, and how they have evolved over time. Additionally, it examines the role of magic spells in literature and popular culture, highlighting their enduring fascination and influence. Finally, the article considers the ethical considerations surrounding spell casting and the controversy surrounding its practice. Overall, this article provides a comprehensive overview of the rich and complex history of magic spells in the English language.
Keywords: Anglo-Saxons, Druids, Normans, myth, wizard, magic, spell, charm, incantation, enchantment, occult, curse, hex, jinx, witchcraft.